Urban Governance and Renewable Energy for Sustainable City Planning and Management - Shahad Faiz Alamry; Samer H. Kadhim Al-Jashaami (Journal of Human, Earth, and Future)
In recent years, significant transformations have occurred in urban systems and their management by enhancing and developing governance through a comprehensive and organized framework based on multiple studies and methods in city management, particularly in the environment and energy sectors. To achieve a balance in the utilization of natural resources and improve the quality of life, the research aims to transform energy into sustainable forms, known as renewable energies, through urban governance as a transitional approach in traditional energy systems and the establishment of long-term sustainable planning systems through self-organizing governance work. This method enables all city sectors to rely on clean energy sources by creating digital governance maps to determine the future directions of cities, bridge gaps, and solve pollution problems and environmental issues. The goal is to develop flexible cities with advanced communications technology and digital governance capable of managing their systems independently. These efforts provide an organized and integrated approach to sustainability assessment, which is an essential part of the city planning process, including the classification and evaluation of alternatives and plans. By analyzing data through SPSS and utilizing Cronbach's Alpha, the research evaluates energy-related factors affecting the sustainability of cities by assessing suitability and quality criteria.